Assessing uncertainty in forecasts of refugia for Joshua trees using high‐density distribution data - Daniel F. Shryock; Todd C. Esque; Gabrielle A. Berry; Lesley A. DeFalco (Ecosphere)
Abstract Joshua trees (Yucca brevifolia and Yucca jaegeriana) are iconic, foundational species of the Mojave and Sonoran Deserts in North America. Due to their ecosystem importance, long generation times, and low resilience to disturbance, these hybridizing sister species are increasingly the focus of conservation efforts. Predicting Joshua tree responses to impending climate variability, along with the extent of suitable future habitat and/or climate refugia, is critical to ongoing management planning. Previous modeling efforts have been hampered by incomplete distribution data and are now out‐of‐date with the most recent global climate projections. We used a high‐resolution, field‐validated distributional database of nearly complete presence and absence records, along with a simulation of dispersal, to project Joshua tree distributions into future time periods and Coupled Model Intercomparison Project phase 6 (CMIP6) emissions scenarios. Overall, our models predict widespread habitat loss with limited availability of newly suitable habitat. Under the highest emissions scenario (SSP5–8.5), we project that up to 80% of current habitat may become unsuitable by 2100. Even so, our models predict a larger area of potential refugia than some previous efforts, particularly in the southern parts of the range, where we project persistent refugia through 2100. We also found a non‐negligible influence of baseline climate period (the period used to represent “current” climate) on predicted future habitat probabilities. Simulations of dispersal based on the Joshua tree's limited capacity suggest that over 25% of suitable future habitat could be inaccessible, while much of the remaining future habitat area consists of refugia within the upper elevations of the species' current range. An increasing frequency of wildfire appears to be the greatest rangewide threat to future suitable habitat for Joshua trees, followed by renewable energy development. Over 80% of future suitable habitat occurs on federally managed lands, including up to 47% within Bureau of Land Management‐administered areas and 15% within National Park Service units.